Proceedings of the natural resources modeling symposium - DeCoursey, Donn G., editor; Shortgrass Steppe symposium, author; SGS-LTER, Colorado State University, publisher (Colorado State University. Libraries, 1985)
In the last few years, scientists in the Agricultural Research Service, ARS-USDA, have developed several mathematical models of field and small watershed response. The models have simulated the hydrologic, erosion, crop growth, and water quality characteristics representative of various land use and treatment scenarios. Most of the model development was in response to needs of the Soil Conservation Service (SCS); regulatory agencies, such as the Environmental Protection Agency (EPA); and other action agencies. In some cases, models have been developed to aid research programs by providing an analytical description of the physical processes being investigated. Recent model development has been rapid; it involves many disciplines and requires scientists from different backgrounds to work together. The Symposium was structured as a forum within which scientists could discuss the technical aspects of their work and compare ideas. It also provided the Soil Conservation Service an opportunity to learn more about the models that are being developed and an opportunity to describe what they need. The first part of the symposium, about two and one-half days, presented an overview of various ARS modeling and related programs and SCS efforts to incorporate them into their programs. The second part of the symposium, about one and one-half days, consisted of four concurrent sessions: chemical and biological processes, soil-water-plant relations, hydrology, and erosion. Presentations in the four concurrent sessions were selected to present the state-of-the-art and research needs as they exist in ARS and SCS.
1983 SGS-LTER natural resources modeling symposium
ARS-30.
April 1985.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Symposium was held in Pingree Park, Colorado on October 16-21, 1983.
Keywords: long term ecological research; shortgrass steppe; grassland ecology; Pawnee National Grassland; Central Plains Experimental Range